(+)-Catechin potentiates the oxidative response of Acinetobacter baumannii to quinolone-based antibiotics. (February 2019) - Ibitoye, O.B.; Ajiboye, T.O.
Abstract: (+)-Catechin is a versatile compound with its pharmacophore (catechol and resorcinol) responsible for prooxidant and antibacterial activities. In this study, we present that demonstrating the synergistic interaction between (+)-catechin and quinolone-based antibiotics, ciprofloxacin and gemifloxacin is related to reactive oxygen species generation. The minimum inhibitory concentration of (+)-catechin against Acinetobacter baumannii AB5075 were considerably lowered for Δ sodB and Δ katG mutants. Checkerboard assay shows synergistic interactions between (+)-catechin and quinolones. (+)-Catechin amplified quinolones-induced redox imbalance by increasing superoxide ion generation, NAD+/NADH ratio and ADP/ATP ratio. Conversely, the level of reduced glutathione was significantly lowered. We conclude that (+)-catechin potentiates quinolone-based antibiotics-induced oxidative stress in A. baumannii by increasing ROS generation, energy metabolism and electron transport chain activity with a concomitant decrease in glutathione. Graphical abstract: Image 1 Highlights: (+)- Catechin synergies quinolone-based antibiotics. (+)-Catechin enhanced quinolines-mediated reactive oxygen species generation. (+)- Catechin enhanced quinolines-induced respiratory chain activity.